BIM-driven energy simulation and optimization for net-zero tall buildings: sustainable construction management - Sajjad, Muhammad; Hu, Anfeng; Alshehri, Abdullah Mohammed; Waqar, Ahsan; Khan, Abdul Mateen; Bageis, Abdulrahman S.; Elaraki, Yassir G.; Shohan, Ahmed Ali A.; Benjeddou, Omrane (Frontiers in Built Environment, 2024)
The growing demand for sustainable and energy-efficient buildings, particularly in the context of tall structures, has prompted increased attention to innovative solutions. Despite advancements in Building Information Modelling (BIM) technology, there exists a critical gap in understanding its comprehensive application for achieving net-zero energy consumption in tall buildings, particularly in the Malaysian construction industry. This research addresses this gap by presenting a novel strategy that integrates BIM technology with energy analysis tools for net-zero tall buildings in Malaysia. The aim of the study is to contribute valuable insights to the construction industry, policymakers, and researchers by conducting empirical research, utilizing case studies, validating the proposed framework, advancing sustainable design practices, and supporting the transition towards net-zero energy tall buildings in Malaysia.The methodology involves a three-phase approach, including qualitative analysis, a pilot survey, and a main questionnaire. Exploratory factor analysis (EFA) validates the categorization derived from qualitative interviews, while Partial Least Squares Structural Equation Modelling (PLS-SEM) assesses the convergent and discriminant validity of the measurement model. Hypotheses testing using bootstrapping establishes the significance of correlations between BIM deployment and key factors such as early design integration, enhanced energy efficiency, optimized system integration, predictive performance analysis, and validation of sustainable design.The research findings support the positive associations between BIM deployment and the mentioned factors, providing statistical significance through T-statistics and P-values. The implications of this research extend beyond the Malaysian context, offering valuable insights for architects, engineers, and stakeholders involved in designing and managing sustainable tall buildings. By addressing the identified gaps and leveraging BIM technology effectively, stakeholders can contribute to the construction of net-zero energy structures, aligning with global efforts towards sustainable and energy-efficient building practices.